2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30896
|View full text |Cite
|
Sign up to set email alerts
|

Professional and Personal Use of Reflection by Engineering Faculty, Students, and Practitioners

Abstract: where he teaches courses in synthetic and biological polymers, materials selection, and fracture mechanics. He has conducted educational research in the areas of ethical decision making, reflection and innovative pedagogies for the past 19 years. He serves as Associate Editor of the journal Advances in Engineering Education. He has served as division chair for the Community Engagement Division and Materials Division of ASEE. Dr. Harding was invited to deliver a workshop on Ethics in the Engineering Curricula a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…These results align with previous results from the literature on student free-response definitions of reflection, with Carberry et al having found 79% of such responses associated with "looking back" (Look Back Remember) and 21% associated with "affecting the future" (Improve Apply) (Carberry et al, 2018). These results showed that surface-level descriptions of reflection, such as "remembering" or "looking back on past actions," were the most-frequently stated definitions by students.…”
Section: Pre Survey Responsessupporting
confidence: 89%
See 2 more Smart Citations
“…These results align with previous results from the literature on student free-response definitions of reflection, with Carberry et al having found 79% of such responses associated with "looking back" (Look Back Remember) and 21% associated with "affecting the future" (Improve Apply) (Carberry et al, 2018). These results showed that surface-level descriptions of reflection, such as "remembering" or "looking back on past actions," were the most-frequently stated definitions by students.…”
Section: Pre Survey Responsessupporting
confidence: 89%
“…The emergent coding scheme developed has similarities to previous work and perspectives in the literature on reflection. For example, Carberry et al developed a coding scheme for student responses to the question of how they used reflection (Carberry et al, 2018). This scheme has several categories in common with the categories in the coding scheme for the present work, including Remembering and Improvement.…”
Section: Literature Basis For Coding Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Deep meaning-making does not come easily for most people, and most do not inherently understand the value. Approximately 20% to 30% of undergraduate engineering students identify reflection as no more than a means of looking back (Carberry et al, 2018;Dickerson et al, 2020), failing to recognize its utility for gaining new insight and directing future choices. Therefore, numerous reflection experiences are necessary to understand the value of reflection to one's learning and practices, consciously make the time for it, recognize when one's thinking is shallow, and employ effective self-prompting to go deeper.…”
Section: Learning Mechanismsmentioning
confidence: 99%
“…Recent research suggests reflection is interesting in practice as well as theoretically. Carberry and his colleagues reported on a study to address how engineering educators, students, and practitioners define reflection and use it in their personal, professional and/or academic life [7]. Their results showcase how students, faculty, and practitioners perceive their use of reflection.…”
Section: Related Workmentioning
confidence: 99%